2010
DOI: 10.1155/2010/807850
|View full text |Cite
|
Sign up to set email alerts
|

Occlusion and Temporomandibular Function among Subjects with Mandibular Distal Extension Removable Partial Dentures

Abstract: Objective. To quantify effects on occlusion and temporomandibular function of mandibular distal extension removable partial dentures in shortened dental arches. Methods. Subjects wearing mandibular extension removable partial dentures (n = 25) were compared with subjects with shortened dental arches without extension (n = 74) and with subjects who had worn a mandibular extension removable partial denture in the past (n = 19). Subjects with complete dentitions (n = 72) were controls. Data were collected at base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
1
15
0
5
Order By: Relevance
“…Most evidence, however, was derived from crosssectional studies and was scored as very low by the authors. Moreover, BES results are in agreement with the results of the studies included (23,26) in the systematic review, which also revealed that occlusion changes were self-limiting and became stable with time. This body of evidence might therefore support the conducting of a well-designed and robust RCT including the non-therapy approach, with the objective of confirming, or not, previous findings on SDA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Most evidence, however, was derived from crosssectional studies and was scored as very low by the authors. Moreover, BES results are in agreement with the results of the studies included (23,26) in the systematic review, which also revealed that occlusion changes were self-limiting and became stable with time. This body of evidence might therefore support the conducting of a well-designed and robust RCT including the non-therapy approach, with the objective of confirming, or not, previous findings on SDA.…”
Section: Discussionsupporting
confidence: 86%
“…One (20) reported SD only. One (23) reported SD and SE. Two studies did not report any measure of imprecision (21,22).…”
Section: So Significant Indirectness Was Not Found In This Sample Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6][7][8] Arguments for not extending SDA with distal-extension RDP are potential risk for deterioration of abutment teeth, not contributing to long-term stable occlusion, and perceived limited 'added value' resulting in not wearing the RDP. [9][10][11][12] It has been estimated for the United Kingdom, that some 30 to 50% of patients never or only occasionally wear their RDP. 12 Regarding masticatory ability, only approximately 10% of subjects with moderate SDA reported complaints on chewing function, mainly for chewing hard foods.…”
Section: Introductionmentioning
confidence: 99%
“…5(12), 88-100 89 of the molar teeth 16 . Contrary, several studies and reviews have indicated that twenty occluding teeth provide sufficient oral functional ability and the need to replace all missing posterior teeth has been questioned 1,7,11,14,[16][17][18][19][20] When dentists extend or reconstitute reduced, shortened or discontinuous dental arches and replace missing teeth in either anterior or posterior regions to create a complete dental arch (CDA), the following interventions are usually recommended: removable partial denture prosthesis (RPDP) or cantilever fixed denture prosthesis (CFDP), including resin-bonded bridges and implant-retained fixed partial dentures (IFPDs) 18,21,22 .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%